Precision Surgery for Placenta Previa Complicated with Placenta Percreta - Juan-Juan Chen; Lin Yu; Chun-Hong Su; Chun-Fang Zhang; Yan-Hong Chen; Yan-Mei Zhou; Wen-Jun He; Fang He; Ting Song; Shou-Ping Wang; Zhi-Yuan Su; Qing-Ping Jiang; et al. (Wolters Kluwer Health, 2019)
Abstract. Objectives:. To investigate whether a precise circular resection of the uterine tissue at the placental attachment part is effective in cases with placenta previa complicated with placenta percreta (PPWPP). Methods:. Patients diagnosed with PPWPP were assessed for pregnancy termination at 34-36 weeks of gestation. During the operation, we performed circular resection of the uterine tissue at the placental attachment part. Then the characteristics of the operation and the follow-ups were recorded. Results:. During the operation, the vital signs were stable. The mean intraoperative blood loss, packed red blood cells units transfusion, fresh frozen plasma transfusion, and operation time were 2140 mL, 6 U, 440 mL, and 179.8 minutes, respectively. There was no bowel, ureter, or bladder injury. And there was no patient transferred to the ICU after operation. The mean postoperative blood loss was 458.6 mL. There was no fever, infection, intestinal obstruction, or other complications after operation during the hospitalization. The shape and the blood flow of the uterus were normal. After the patients were discharged, one had developed cesarean scar diverticulum. The mean lochia duration was 30 days. The menstrual cycle and volume were as before. The shape and the blood flow of the uterus and the ovarian were normal. Conclusions:. The circular resection following end-to-end anastomosis is an effective precision surgical approach for PPWPP. It can achieve the purpose of hemostasis while maximizing the protection of organ function and reducing surgical trauma.